PELAYANAN PENGASUH TERHADAP ANAK DI PANTI ASUHAN PUTRI AISYIYAH DAERAH KAMPAR - Sari, Intan; Achmad, Said Suhil; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Problem formulation in this research is how is the process of care services for children in Putri Aisyiyah Orphanage in Kampar area ?. This study aims to explore the process of caring for children in the Putri Aisyiyah Orphanage in the Kampar area. This study uses a qualitative approach with a descriptive type. The informant selection technique in this study uses a purposive sampling technique. The informants in this study are people who are involved and have the information needed in the study, because the informants are people who are more knowledgeable about the issues to be studied. Data collection techniques used were observation, interviews, and documentation, and triangulation of child care services at the Putri Aisyiyah Orphanage in the Kampar area. This study consists of one variable, namely the indicators (1) self-esteem, (2) meeting expectations, (3) improvement, (4) foresight, (5) improvement, (6) attention, (7) empowerment. The subjects of this study were 3 people consisting of 1 core informant and 2 control informants. From the results of research conducted, it can be concluded that: the care service process that appears there are only 5 aspects, while 2 aspects do not appear because it is not found in the service process provided by caregivers for children in the Putri Aisyiyah Orphanage in the Kampar area. Implementation of care services that often arise are caregivers instructing children to directly work on duty picket, giving advice to foster children who do not want to work when mutual cooperation, caregivers provide improvement by listening to complaints foster children, caregivers use technology as much as possible, and caregivers give rewards to children foster achievers. In this care process the most important thing in care is the chairman of Putri Aisyiyah Orphanage, secretary, treasurer, nurturing section, education section, and skills section.Key Words: Service, Caregivers, Children